Effectiveness of Cream Preparations Combination of Bay Leaf Extract (Syzygium polyanthum Wight) and Papaya Leaf (Carica Papaya L) as Anti-Inflammation - Samodra, Galih; Kusuma, Ikhwan Yudha; Melani, Reina (Journal of Advanced Health Informatics Research, 2023)
Bay leaves (Sygyzium polyanthum Wight) and papaya leaves (Carica papaya L) are plants that have anti-inflammatory activity due to their flavonoid compounds. The purpose of this study was to determine the formulation of bay leaf and papaya leaf extracts into cream preparations. The treatment group consisted of 4 groups. The first group is the positive control (voltarene), the second group is the negative control (1% carrageenan). The third group was the group that was given the combination cream treatment of bay leaf and papaya leaf extract formula 2 and the fourth group was the group that was given the cream treatment combination of bay leaf and papaya leaf extract formula 3. The anti-inflammatory test was carried out based on observations for six hours by looking at edema volume and edema percentage. LSD test results showed that the cream formula 2 treatment (anionic) and the cream formula 3 treatment (nonionic) showed a significant difference with the negative control with a significance value of 0.000 (p <0.05). This shows that formula 2 cream treatment (anionic) and formula 3 cream treatment (nonionic) can potentially reduce edema volume and can inhibit edema on the soles of rats induced with carrageenin